Integration of satellite remote sensing data for gold prospecting in tropical regions - Pour, Amin Beiranvand (2015)
The area under investigation is the Bau gold mining district in the State of Sarawak, East Malaysia, on the island of Borneo. It has tropical climate with limited bedrock exposures and the other constraints imposed in the environment. Bau is a gold field with Carlin style gold deposits. Geological analyses coupled with remote sensing data were used to detect structure elements and hydrothermally altered rocks associated with gold mineralization. The Landsat Enhanced Thematic Mapper + (ETM+), the Phased Array type L-band Synthetic Aperture Radar (PALSAR) and the Hyperion data were integrated to carry out lithological-structural mapping of mineralized zones in the study area and surrounding terrains. Hydrothermally alteration mineral zones were detected along the SSW to NNE structural trend of the Tai Parit fault that corresponds to the areas of occurrence of the gold mineralization in the Bau Limestone. The results show that the known gold prospects and potentially interesting areas are recognizable by the methods used, despite limited bedrock exposure in this region and the constraints imposed by the tropical environment. The approach used in this study can be more broadly applicable to provide an opportunity for detecting potentially interesting areas of gold mineralization using the integration of ETM+, PALSAR and the Hyperion data in the tropical/sub-tropical regions.